600 °C Operation of a LDMOS Integrated on a 4H-SiC CMOS Platform - Kammel, Robert; Dick, Jan; May, A.; Rommel, M.; Schulze, Jörg (2025 MIPRO 48th ICT and Electronics Convention, MIPRO 2025 - Proceedings, 2025)
Laterally "diffused"metal oxide semiconductor transistors (LDMOS) play an important role for the integration of power electronics in integrated circuits, due to their lateral structure matching the CMOS design architecture. This work demonstrates the successful fabrication of LDMOS transistors on 4H-SiC and their operation at temperatures up to 600 C. That capability allows power devices to operate at higher temperatures beyond the limits of Silicon MOSFETs, eliminating the need for complex cooling systems for the integrated circuit. In this work, low threshold voltage shift, especially for operation temperatures above 300 C, temperature dependence of the on-state resistance and the saturation current, as well as permanent degradation processes are discussed.
CRIS-Team Scopus Importer:2025-10-03
Keywords: 4H-SiC; CMOS platform; high-temperature operation; LDMOS